Evaluation approach for network components performance using trustworthiness measurement - Gang XIONG; Ju-long LAN; Yu-xiang HU; Shi-ran LIU (Tongxin xuebao)
For the network components selecting problem involved the process of building the new network and net-work service,a network component evaluation method was proposed based on the trustworthiness measurement and the model of the multiple attribute decision analysis.First of all,according to the flexible characteristics of the network ap-plication environment,an on-demand driven and dynamic strategy was designed for constructing trustworthiness index tree.Secondly,the uncertainty of the subjective weight was reduced by using the fuzzy analytic hierarchy process,and the combination weight calculated from the subjective objective weight was used to improve the fairness of weight-ing operation.Next,in the decision stage,the evaluation results were obtained through the integrated use of processing strategies which include the index data utility transformation,the trustworthiness attribute vector construction and the calculation of vector relative approximation degree.Finally,the rationality,applicability and validity of the presented ap-proach are demonstrated with the evaluation of the software defined network controllers,and the results contribute to provide operators more decision information.